Work-based learning as a pathway to competence-based education : a UNEVOC Network contribution - Bahl, Anke [Herausgeber]; Dietzen, Agnes [Herausgeber] (Bundesinstitut für Berufsbildung, 2019)
"This book provides a rich collection of research and practice perspectives around central topics in the field of work-based learning (WBL). Based on an extensive prior literature review of the current state of research on WBL in TVET contexts on a global scale, key themes of interest for a competence-based perspective were chosen to call for contributions from researchers and experts in VET from all around the world. Inspired by research evidence from a diversity of recent national projects, the book offers new insights in conducive factors for learning on the level of the individual subject and the work environment. The papers pick up regional and national challenges in supporting WBL and in developing and implementing curricula based on actual work processes. They take a closer look at the role of tutors in WBL and show new options in the transfer and recognition of knowledge, skills and competences. The research approaches presented in this book are meant to support everyone in meeting their TVET objectives, regardless of region and scale." (Editor)
Keywords: L 2.1.1 Informelles Lernen; I 2.2.1 Westeuropa; I 2.3.1 Afrika; I 2.3.4 Asien; Betriebliche Berufsausbildung; Lernen am Arbeitsplatz; Kompetenzorientierung; Digitalisierung; Ausbildungszufriedenheit; Ausbilder; Trainer; Professionalisierung; Informelles Lernen; Anerkennung; Dänemark; Vereinigtes Königreich; Subsahara-Afrika; Nigeria; Singapur; Argentinien; China; Bundesrepublik Deutschland